2000
DOI: 10.1109/82.877148
|View full text |Cite
|
Sign up to set email alerts
|

A high-speed conditional carry select (CCS) adder circuit with a successively incremented carry number block (SICNB) structure for low-voltage VLSI implementation

Abstract: This paper reports a conditional carry select (CCS) adder circuit with a successively-incremented-carry-number block (SICNB) structure for low-voltage VLSI implementation. Owing to the successively-incremented-carry-number block (SICNB) structure, the new 16-bit SICNB CCS adder provides a 37% faster speed as compared to the conventional conditional carry select adder based on the SPICE results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…3 shows the structure of improved Wallace tree. The structure is good in symmetry, regularity and easy implement for layout [5].…”
Section: The Design Of Structure and Algorithm Researchmentioning
confidence: 99%
“…3 shows the structure of improved Wallace tree. The structure is good in symmetry, regularity and easy implement for layout [5].…”
Section: The Design Of Structure and Algorithm Researchmentioning
confidence: 99%
“…A hybrid CLA/ CSA proposed by Wang, Pai, and Song (2002) reduces 1/3 of the critical path delay compared to conventional adders, but its area and power penalty is higher because of its CLA unit. Similarly, Poli (2004, 2011) and Huang and Kuo (2000) proposed different design approaches for CSA for minimising its delay but not on optimising its power and area.…”
Section: Introductionmentioning
confidence: 98%
“…A CPU's adder circuit is largely responsible for its speed performance. It has been observed that cer-2 tain adder circuits can perform faster [3] but with more Power consumption. To address the issues with power usage, a FinFET based carry select adder (CSA) is proposed which consumes less power than MOSFET [4].…”
Section: Introductionmentioning
confidence: 99%
“…The SUM generated by HA0 and Ex1_0 adder is given to 2-1M _1 which produces S[0] and then CARRY generated by HA0 and Ex1_0 is given to 2-1M_2 which produces C[0].In this PCSA the Carry propagation is done through The generated C[0] is propagated through 2-1M_3 which provides S[1] as output with respect to Cin (0 or 1). Similarly, S[2], S[3], and C[1], C[2], Cout are generated. (i) CMOS Excess-1 adder using 2-1M (ii) TGL Excess-1 adder using 2-1M…”
mentioning
confidence: 99%